A crosstalk between circular RNA, microRNA, and messenger RNA in the development of various brain cognitive disorders - He, Liang; Zhang, Furong; Zhu, Yuling; Lu, Meilin (Frontiers in Molecular Neuroscience, 2022)
Patients with Alzheimer's disease (AD), Parkinson's disease (PD), traumatic brain injury (TBI), stroke, and postoperative neurocognitive disorder (POND) are commonly faced with neurocognitive disorders with limited therapeutic options. Some non-coding ribonucleic acids (ncRNAs) are involved in the development of various brain cognitive disorders. Circular RNAs (circRNAs), a typical group of ncRNAs, can function as competitive endogenous RNAs (ceRNAs) to dysregulate shared microRNAs (miRNAs) at post-transcription level, inhibiting regulation of miRNAs on their targeted messenger RNAs (mRNAs). circRNAs are abundant in central nervous system (CNS) diseases and cause brain disorders, but the exact roles of circRNAs are unclear. The crosstalk between circRNA, miRNA, and mRNA plays an important role in the pathogenesis of these neurocognitive dysfunction diseases and abnormal conditions including AD, PD, stroke, TBI, and POND. In this review, we summarized the participation of circRNA in neuroglial damage and inflammation. Finally, we aimed to highlight the regulatory mechanisms of circRNA–miRNA–mRNA networks in the development of various brain cognitive disorders and provide new insights into the therapeutics of these diseases.